Declining subscriptions to the Maliando Mutual Health Organisation in Guinea-Conakry (West Africa): what is going wrong? - Criel, Bart; Waelkens, Maria Pia (Social science & medicine (1982), 2003)
Mutual Health Organisations (MHOs) are a type of community health insurance scheme that are being developed and promoted in sub-Saharan Africa. In 1998, an MHO was organised in a rural district of Guinea to improve access to quality health care. Households paid an annual insurance fee of about US$2 per individual. Contributions were voluntary. The benefit package included free access to all first line health care services (except for a small co-payment), free paediatric care, free emergency surgical care and free obstetric care at the district hospital. Also included were part of the cost of emergency transport to the hospital. In 1998, the MHO covered 8% of the target population, but, by 1999, the subscription rate had dropped to about 6%. In March 2000, focus groups were held with members and non-members of the scheme to find out why subscription rates were so low. The research indicated that a failure to understand the scheme does not explain these low rates. On the contrary, the great majority of research subjects, members and non-members alike, acquired a very accurate understanding of the concepts and principles underlying health insurance. They value the system's re-distributive effects, which goes beyond household, next of kin or village. The participants accurately point out the sharp differences that exist between traditional financial mechanisms and the principle of health insurance, as well as the advantages and disadvantages of both. The ease with which risk-pooling is accepted as a financial mechanism which addresses specific needs demonstrates that it is not, per se, necessary to build health insurance schemes on existing or traditional systems of mutual aid. The majority of the participants consider the individual premium of US$2 to be fair. There is, however, a problem of affordability for many poor and/or large families who cannot raise enough money to pay the subscription for all household members in one go. However, the main reason for the lack of interest in the scheme, is the poor quality of care offered to members of the MHO at the health centre.